2019
DOI: 10.1111/cge.13635
|View full text |Cite
|
Sign up to set email alerts
|

The genome empowerment scale: An assessment of parental empowerment in families with undiagnosed disease

Abstract: While genomic sequencing (ES/GS) has the potential to diagnose children with difficult to diagnose phenotypes, the goal should be not only a diagnosis, but also to empower parents to seek next steps for their children and to emotionally manage the outcome, whether or not a diagnosis is secured. To help achieve this goal, objective measures are needed to assess the process of parental empowerment related to genome sequencing. We present the validity and reliability of the Genome Empowerment Scale (GEmS), develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…As reported previously, validation assessments of the GEmS with parents of children undergoing ES/GS for diagnostic purposes found that it had good psychometric properties (McConkie‐Rosell et al., 2019) and was consistent with the theoretical foundation of healthcare empowerment (Johnson, 2011; Johnson et al., 2012). The GEmS consists of 28 items, each evaluated on a Likert scale from 1 (low) to 7 (high).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…As reported previously, validation assessments of the GEmS with parents of children undergoing ES/GS for diagnostic purposes found that it had good psychometric properties (McConkie‐Rosell et al., 2019) and was consistent with the theoretical foundation of healthcare empowerment (Johnson, 2011; Johnson et al., 2012). The GEmS consists of 28 items, each evaluated on a Likert scale from 1 (low) to 7 (high).…”
Section: Introductionsupporting
confidence: 59%
“…Additionally, the complexity of the discussion for ES/GS consent is difficult to balance with specific tailoring of the genetic counseling due to psychosocial factors such as the individual's coping strategies and social support (Macnamara et al., 2019; Schmidlen et al., 2018). These findings led us to develop the Genome Empowerment Scale (GEmS) (McConkie‐Rosell et al., 2019) as patient‐reported tool to assess genomic healthcare empowerment in adult probands/parents of children with undiagnosed disorders about to undergo ES/GS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the dimensions of the GCOS (i.e., cognitive, decisional and behavioural control, emotional regulation, and hope) reflect on non-health-related benefits of genetic counselling and overlap with dimensions identified by Kohler and by our review, the measures are not specific to the impact of genetic testing, rather they are focused on the impact of genetic counselling services. Using a different theoretical underpinning than the GCOS and GOS, McConkie-Rosell et al developed the Genome Empowerment Scale (GEmS) [ 72 ]. While this tool was designed to understand parents’ perspectives on the process of empowerment in the context of genetic testing, it is administered prior to testing and does not reflect on the actual impact of test results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whether or not elements of these constructs are distinct from or overlapping with elements of clinical utility or with elements of psychosocial well-being remains contested [ 9 , 16 , 63 ]. In addition, some orient to personal and perceived utility as measures of anticipated (i.e., pre-test) value [ 72 , 73 ], some as a measure of actual (i.e., post-test) value [ 15 , 20 , 74 , 75 ], and some as a composite of both [ 16 , 17 , 70 , 71 ]. Finally, whether any one of these constructs can be applied to a range of clinical genetics settings and respondent types or whether tailored approaches are required to achieve face validity in a range of settings requires further consideration.…”
Section: Discussionmentioning
confidence: 99%